Tuğrul Tanyol: la bellezza è una presa di posizione - Nicola Verderame (Lea, 2015)
This short article outlines the life and work of Tuğrul Tanyol, a prominent living Turkish poet and one of the protagonists of the generation of poets who started their activity in the 1980s. In presenting the main biographical, stylistic, and thematic aspects of Tanyol’s decades-long career, this article aims at making the Italian reader familiar with Tanyol’s poetic world. A selection of his poems is presented in Italian translation.